If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8a + 3 = 3(4 + a) Reorder the terms: 3 + 8a = 3(4 + a) 3 + 8a = (4 * 3 + a * 3) 3 + 8a = (12 + 3a) Solving 3 + 8a = 12 + 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. 3 + 8a + -3a = 12 + 3a + -3a Combine like terms: 8a + -3a = 5a 3 + 5a = 12 + 3a + -3a Combine like terms: 3a + -3a = 0 3 + 5a = 12 + 0 3 + 5a = 12 Add '-3' to each side of the equation. 3 + -3 + 5a = 12 + -3 Combine like terms: 3 + -3 = 0 0 + 5a = 12 + -3 5a = 12 + -3 Combine like terms: 12 + -3 = 9 5a = 9 Divide each side by '5'. a = 1.8 Simplifying a = 1.8
| In(2x)+in(x)=in(8x) | | 2500y+55000=2000y+62000 | | 53=8w+5 | | 8m^2+s^2=2t | | 53=8+5 | | 4t=1o-t | | 1200m+1000=1175m+1500 | | 12.50+.40e=14.75+.25c | | 0.1y=0.2x+1 | | 3.5g+2=3.25g+5 | | 19+45= | | .20p+7=.30p+5 | | 6m+200=-6m+5.00 | | .99d=.89d+10 | | k^4+5*k^3+5*k^2-5*k-6=0 | | (-3f^2+4f-3+8f^2+7f+1)= | | 7y-3=4y+12 | | 6a+42=5a-15 | | 3p+7=1 | | 3(x+1)=-x+31 | | -24=2(3x+5)+8 | | 10a-20-9a+6=0 | | 6x+y=25 | | -4x-7=-15 | | 2x-37=5(x-2) | | 5/y+1/5=9/y | | 9a-6=4a-16 | | 3x+21+x+3=18 | | 3x/5+2x/5=4.20 | | 2a+2+a+3=8 | | 36K^2-36+108k=0 | | 7x-56=6x+12 |